Pathological Characteristics of Fiberoptic Bronchoscopy Procedure in Ulin General Hospital, Banjarmasin - Ira Nurrasyidah; Muhammad Ajib Nuzula; Ika Kustiyah Oktaviyanti; Desi Rahmawaty; Tenri Ashari Wanahari (Jurnal Respirasi, 2023)
Introduction:  Fiberoptic Bronchoscopy (FOB) has emerged into the method of choice for the detection of lung tumors due to its availability of Adequate cytological and histological samples in the form of broncho-alveolar lavage, bronchial brushings, and bronchial forceps biopsy. This study aims to identify characteristics of bronchoalveolar lavage, aspiration cytology, brushing cytology and forceps cytology of patients suspected with malignancy at the Ulin Regional Hospital in South Kalimantan. Methods: A cross-sectional study was carried out utilizing medical documentation of patients suspested lung cancer from March 2018 to March 2020. Data were grouped by gender, age, type of procedure, and cytology and histopathology findings. Results: The result showed that 67.5% of 117 patients who underwent bronchoscopy had positive results and common histological diagnosis The frequent histopathological conclusion was adenocarcinoma (45.6%) tailed by squamous cell carcinoma (40.55). Forceps bronchoscopy showed a greater positivity rate (75.0%) than bronchoscopy without forceps (63.6%), we also found that by combining BAL and brushing and forceps biopsy, the detection rate of lung malignancy increased to 85.7%, but no correlation between the type of procedure and the likelihood of malignancy was discovered. Conclusions: Forceps bronchoscopy showed a greater positivity rate than bronchoscopy without forceps, but no correlation between the type of procedure and the likelihood of malignancy was discovered in our study.